Effects of Sodium and Chloride on Nursery Pigs Growth Performance - Moniz, Madison M.; Shawk, Dwight J.; Goodband, Robert D.; Clark, Anne B. (My University, 2016)
Sodium and chloride provide assistance in regulating osmotic pressure within cells. If either sodium or chloride are deficient in the diet, appetite and growth performance will be decreased. The NRC (2012) recommends that there must be at least 0.35% sodium and 0.45% chloride in diets for nursery pigs weighing 15 to 25 lb. Therefore, our study was designed to evaluate the individual influence of sodium and chloride on growth performance of phase 2 nursery pigs. A total of 360 pigs were used in a 14-day trial at the KSU Swine Teaching and Research Center. Each pen contained 6 pigs with an average initial weight of 15 lb. A total of 4 treatments were randomly distributed with a total of 15 replications per treatment. The positive control diet contained 200 lb/ton of dried whey with 12 lb/ton of added salt (0.37% sodium and 0.67% chloride). The negative control diet contained 144 lb/ton of lactose with 7 lb/ton of added salt (0.18% sodium and 0.35% chloride). The two additional diets were the negative control plus either 15.5 lb/ton of salt (0.37% sodium and 0.60% chloride) or 23 lb/ton of sodium bicarbonate and 8 lb/ton of potassium chloride (0.37% sodium and 0.35% chloride). The negative control diet with 15.5 lb/ton of added salt was used to meet the sodium requirement but exceeded chloride requirement. Pigs fed the positive control diet or the negative control diet with 15.5 lb of added salt had similar ADG, and ADFI which was greater (P < 0.05) than the pigs fed the negative control diet with 7 lb of added salt. Pigs fed the negative control diet with 15.5 lb of added salt and the negative control with potassium chloride and sodium bicarbonate were intermediate. Pigs fed the negative control diet with 15.5 lb of added salt had the best feed efficiency (P < 0.09), while pigs fed the positive control diet had the poorest feed efficiency. Pigs fed the negative control diet with 7 lb of added salt and the negative control diet with potassium chloride and sodium bicarbonate were intermediate. These results imply that if a nutritionist is designing a diet for nursery pigs from 15 to 25 lb the NRC (2012) standards sodium must be 0.35% in order to maximize ADG and ADFI.
Keywords: Fall 2016